EARLY STAGES OF INTESTINAL ABSORPTION OF SPECIFIC ANTIBODIES IN THE NEWBORN : An Ultrastructural, Cytochemical, and Immunological Study in the Pig, Rat, and Rabbit - Kraehenbuhl, J. P. (The Rockefeller University Press, 1969)
In mammals, passive immunity is transferred from mother to offspring by transplacental passage or by intestinal absorption. The rabbit receives antibodies exclusively across the placenta, whereas intestinal absorption is the principal source of antibodies for the new-born pig. In the rat, passive immunity is transferred by both pathways. The role of the jejunal absorptive cells was investigated in these three species, by the use of specific immune globulins as tracers of protein absorption. Rabbit anti-peroxidase and anti-ferritin antibodies were injected into the jejunum of newborn pigs, rats, and rabbits, and absorption was studied over the first 2 hr. The specific antibodies were detected in glutaraldehyde-fixed tissues after in vitro treatment with the antigens, and in sera by immunological methods. Intact antibodies are transferred into the circulation of the pig and the rat, but not into that of the rabbit. In the three species, the jejunal absorptive cells take up antibodies by endocytosis. In the pig, the antibodies are transported across the epithelium in vacuoles. In the rabbit, the endocytosis of antibodies triggers a lysosomal response and all absorbed antibodies are trapped in lysosomes. In the rat, both situations are found; there is no evidence of transfer of antibody fragments into the circulation.